2003
DOI: 10.1152/ajpendo.00319.2002
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation and the effect of IGF-I on muscle strength and power in older persons

Abstract: Deregulation of the inflammatory response plays a major role in the age-related decline of physical performance. The causal pathway leading from inflammation to disability has not been fully clarified, but several researches suggest that interleukin-6 (IL-6) causes a reduction of physical performance in elderly through its effect on muscle function. In vitro studies demonstrated that IL-6 inhibits the secretion of insulin-like growth factor I (IGF-I) and its biological activity, suggesting that the negative ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
194
5
9

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 271 publications
(222 citation statements)
references
References 28 publications
8
194
5
9
Order By: Relevance
“…A number of studies have demonstrated that chronically high IL-6 plasma levels in the elderly reduce muscle mass and strength (13,17,18,27) but not in communitydwelling health elderly women. This is the first Brazilian study to investigate whether IL-6 levels are associated with muscle performance and functional capacity in community-dwelling elderly women.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of studies have demonstrated that chronically high IL-6 plasma levels in the elderly reduce muscle mass and strength (13,17,18,27) but not in communitydwelling health elderly women. This is the first Brazilian study to investigate whether IL-6 levels are associated with muscle performance and functional capacity in community-dwelling elderly women.…”
Section: Discussionmentioning
confidence: 99%
“…A number of epidemiological studies have reported an association between high levels of IL-6 and the loss of functional capacity, as well as an increase in mortality rates for elderly people (10,(13)(14)(15)(16). Other studies have demonstrated an association between high levels of IL-6 and reduced muscle strength in the elderly (13,17,18). Haddad et al (19) found atrophy in the tibialis anterior muscle of mice injected locally with relatively low doses of IL-6.…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory marker IL-6, which is associated with sarcopaenia and muscle wasting [18], was elevated in the old rats (P \ 0.05), but was not significantly elevated further after treatment with alfacalcidol. The adiponectin serum concentration was 64% higher in the alfacalcidol group compared to that of the vehicle group (P = 0.004), but was not significantly different from that of the control adult group.…”
Section: Circulating Factorsmentioning
confidence: 94%
“…IL-6 is an inflammatory cytokine and elevated circulating levels have been associated with loss of muscle strength [18,49] and atrophy [42,47]. Treatment with alfacalcidol was, however, not accompanied with an increase in circulating IL-6 levels and alfacalcidol has even been shown to decrease tumor necrosis factor-a [50], another cytokine having a catabolic effect on muscle [42].…”
Section: Effects Of Alfacalcidol and Muscle Fibre Atrophymentioning
confidence: 99%
See 1 more Smart Citation